2005
DOI: 10.22358/jafs/67148/2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the gastrointestinal tract in weaning pigs as affected by crude fibre content in the diet

Abstract: A growth of the gastrointestinal tract of weaned pigs as affected by crude fibre content in the diet was investigated on 16 piglets. Pigs of 10 kg body weight (BW) were offered a basal diet (group C and C 1 ) or diets formed by mixing a basal diet with 10 (diet GM 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For instance, solid feed consumption increased stomach weight in suckling piglets (Cranwell, 1985). Moreover, intake of grass meal fibre (10% and 20% of the diet) positively correlated with stomach weight of weaned piglets (Skiba et al, 2005). Similarly, a diet high in insoluble fibre (from straw and oat hulls) increased relative stomach weight in freshly weaned piglets (Gerritsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, solid feed consumption increased stomach weight in suckling piglets (Cranwell, 1985). Moreover, intake of grass meal fibre (10% and 20% of the diet) positively correlated with stomach weight of weaned piglets (Skiba et al, 2005). Similarly, a diet high in insoluble fibre (from straw and oat hulls) increased relative stomach weight in freshly weaned piglets (Gerritsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, solid feed consumption increased stomach weight in suckling piglets (Cranwell, 1985). Moreover, intake of grass meal fibre (10% and 20% of the diet) positively correlated with stomach weight of weaned piglets (Skiba et al, 2005).…”
Section: Comparative Analysis (Body Weight Stomach Development)mentioning
confidence: 94%
“…Thirdly, dietary fibre may induce growth and functional maturation of the tissues of the GIT (Gerritsen et al, 2012; Jin et al, 1994; Jørgensen et al, 1996; Skiba et al, 2005). Through its bulking effect, viscosity or water‐holding capacity, dietary fibre can alter intestinal transit kinetics, such as through modulating gastric emptying rate or transversal motility supporting gastrointestinal development per se (Kim et al, 2012; Molist et al., 2014; Van Hees et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the positive effect of dietary fiber in term of enhancing intestinal morphology in newly weaned pigs. Many ingredients have been used as dietary fiber sources such as a combination of oat hull and wheat straw (Gerritsen et al, 2012), barley hull (Hedemann et al, 2006) and grass meal (Skiba et al, 2005). Moreover, dietary fiber increases the activity of certain enzymes such as amylase and brush border enzymes in weaned pigs (Gerritsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%